The Relationship Between Self-Knowledge, Occupational Exploration And Career Decision-Making Among Undergraduates - Norida, Abdullah; Aida Nasirah, Abdullah; Zanariah, Jano; Zawiah , Mat; Hanipah , Hussin; Sharif, Mustaffa (Science International, 2014)
This study examined the relationship between self-knowledge (SE), occupational exploration (JSI) and career decision making (CDMSE) among undergraduates. The instruments used for this study were the Rosenberg Self-Esteem Scale, Job-Search Intensity Scale, and Career Decision-Making Self-Efficacy Scale. Participants were recruited using a cluster sampling procedure. The questionnaire was reliable and valid to measure SE, JSI and CDMSE. Data collected from 678 undergraduates were tested with confirmatory factor analysis to obtain three best-fit measurement models from the three latent variables. Subsequently, the structural equation modeling was applied to test the hypotheses. The results showed a strong relationship between SE and CDMSE, a positive relationship between JSI and CDMSE, and a positive relationship between SE and JSI. Implications of the findings for social work practice such as guidance counsellor, research, theory, policy and education were also discussed.